The Generation program: Baseline characteristics of cognitively unimpaired APOE4 carriers recruited for Generation study 1 and Generation study 2: Alzheimer's Prevention Initiative (API) Generation program: Baseline characteristics and umibecestat results during treatment and follow‐up. (7th December 2020) - Tariot, Pierre N.; Borowsky, Beth; Liu, Fonda; Riviere, Marie‐Emmanuelle; Rouzade‐Dominguez, Marie‐Laure; Cazorla, Pilar; Quinn, Matt; Ricart, Javier; Langbaum, Jessica B.; Viglietta, Vissia; Sui, Yihan; Caputo, Angelika; et al.
Abstract: Background: The Alzheimer Prevention Initiative (API) Generation Program evaluated the effectiveness of the BACE1 inhibitor, umibecestat, and the active immunotherapy, CAD106, in delaying the onset of AD symptoms in APOE4 carriers. The Generation Program included two studies implemented in 23 countries at 207 sites. Recruitment in the program and treatment with umibecestat was terminated in July 2019 after detecting an early signal of mild worsening in some measures of cognitive function with umibecestat. We will summarize the baseline characteristics of participants in the Generation Program. Method: Treatment duration was planned for 5‐8 years in two double‐blind, placebo‐controlled, parallel design studies (Lopez Lopez et al., 2019) in cognitively unimpaired participants aged 60‐75 years, at risk for onset of clinical symptoms due to AD. Generation Study 1 (NCT0256551) recruited APOE4 homozygotes (HMs) while Generation Study 2 (NCT03131453) enrolled both HMs as well as APOE4 heterozygotes (HTs) if they also had elevated brain amyloid (assessed by either PET and/or CSF). Both studies included a 12‐week screening phase starting with genotyping. Amyloid testing was the last screening assessment performed before randomization. Result: Among the 9623 participants recruited, more than 2700 completed the 12‐week Screening phase with amyloid testing. Approximately 27% were HMs. About 60% of HMs and 35% of HTs had elevated brain amyloid. A total of 1623 participants were randomized: 478 to Generation Study 1 (all HMs) and 1145 to Generation Study 2 (including 20% HMs and 80% HTs with elevated amyloid). Education, sex, family history of AD, clinical scales (including MMSE, RBANS total score and indices, CDR sum of boxes, and ECog), brain volumes and amyloid status will be shown. Scores from cognitive scales will be presented by sex, genotype (E4/E4, E3/E4, E2/E4), age group and amyloid status. Conclusion: The Generation program collected a broad set of parameters for the world's largest cohort of cognitively unimpaired APOE4 carriers. Baseline characteristics of participants enrolled in the Generation Program were consistent with the target population at risk for AD. Findings in relation to genotype, age, sex and amyloid status will be discussed.